Impurity ion removal with the use of drift resonance - Shishkin, A.A.; Zolotukhin, A.V. (Вопросы атомной науки и техники, 2000)
Impurity ion removal in a toroidal magnetic trap with a helical field under time-dependent magnetic field perturbations is considered using guiding center equations. The ultimate goal is to find out ways to remove impurities from the confinement volume or to protect the confinement volume from impurity ion penetration in stellarator (torsatron) type traps.